Biological Activity, Hepatotoxicity, and Structure-Activity Relationship of Kavalactones and Flavokavins, the Two Main Bioactive Components in Kava (Piper methysticum). (23rd August 2021) - Wang, Yingli; Su, Chao; Zhang, Bo; Niu, Yang; Ren, Ruru; Zhao, Xiaojun; Yang, Lingling; Zhang, Wannian; Ma, Xueqin
Abstract : Kava ( Piper methysticum Forst) is a popular and favorable edible medicinal herb which was traditionally used to prepare a nonfermented beverage with relaxant beneficial for both social and recreational purposes. Numerous studies conducted on kava have confirmed the presence of kavalactones and flavokawains, two major groups of bioactive ingredients, in this miraculous natural plant. Expectedly, both kavalactone and flavokawain components exhibited potent antianxiety and anticancer activities, and their structure-activity relationships were also revealed. However, dozens of clinical data revealed the hepatotoxicity effect which is indirectly or directly associated with kava consumption, and most of the evidence currently seems to point the compounds of flavokawains in kava were responsible. Therefore, our aim is to conduct a systematic review of kavalactones and flavokawains in kava including their biological activities, structure-activity relationships, and toxicities, and as a result of our systematic investigations, suggestions on kava and its compounds are supplied for future research.